The Effect of Health Promotion on Health Cadres’ Knowledge of Tuberculosis Preventive Therapy in Sukorame, Kediri - Fahira, Aulia; Setyanagara, Adwin (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Pulmonary tuberculosis (TB) remains a major global health challenge and is the second leading cause of death from infectious diseases after COVID-19. In Indonesia, the incidence of TB is among the highest worldwide, with East Java ranked second nationally. Knowledge and adherence to Tuberculosis Preventive Therapy (TPT) are still limited, particularly among communities at risk, making health education crucial. This study aimed to analyze the effect of health promotion on the knowledge of health cadres regarding tuberculosis preventive therapy in Sukorame, Kediri. A pre-experimental analytic study with a one-group pretest-posttest design was conducted among 41 active health cadres. Data were collected through a questionnaire covering knowledge, attitude, and practice related to TPT. Health education was delivered via presentations and leaflets, and knowledge was assessed before and after the intervention. The results showed a significant improvement in cadres’ knowledge, with pretest scores indicating poor knowledge in all respondents (100%), while posttest scores showed 52% with good knowledge, 44% with moderate knowledge, and only 4% with poor knowledge. Statistical analysis using the Wilcoxon test confirmed a significant difference (p = 0.000). It can be concluded that health promotion effectively increased health cadres’ knowledge of TB preventive therapy. Continuous monitoring and follow-up are recommended to sustain behavioral changes and strengthen TB prevention efforts.